Literasi Digital dan Budaya melalui Visualisasi Software Batu Kubur Sumba di SMP N 1 Waikabubak - Ayu, Mitra Permata; Rangga, Andreas Ariyanto; Kaka, Roswita Sari; A.K.Dima, Vensensius A.K.Dima (LPPM UMRI, 2026)
Digital literacy and cultural preservation represent contemporary challenges in education that require harmonious integration to achieve optimal learning objectives. This community service activity aims to enhance students' digital literacy and cultural understanding through the visualization of Microsoft Word software using an ethnomathematical approach to Sumba's tombstone artifacts. The method employed in this activity is technology-based learning with a student-centered approach. The results indicate a highly positive response, reflected in the high level of enthusiasm among the students of SMP N 1 Waikabubak in participating in all stages of the training. Furthermore, participants successfully implemented the Shapes feature to reconstruct two-dimensional and three-dimensional shapes found in the tombstone structures, demonstrating an improvement in visual skills, creativity, and numeracy literacy rooted in local wisdom. This activity proves that the integration of simple technology into learning can be an effective means of maintaining the relevance of local culture in the digital era. Keywords: digital literacy, culture, software, tombstone